2023
DOI: 10.1038/s41396-023-01395-z
|View full text |Cite
|
Sign up to set email alerts
|

Climate change-related warming reduces thermal sensitivity and modifies metabolic activity of coastal benthic bacterial communities

Abstract: Besides long-term average temperature increases, climate change is projected to result in a higher frequency of marine heatwaves. Coastal zones are some of the most productive and vulnerable ecosystems, with many stretches already under anthropogenic pressure. Microorganisms in coastal areas are central to marine energy and nutrient cycling and therefore, it is important to understand how climate change will alter these ecosystems. Using a long-term heated bay (warmed for 50 years) in comparison with an unaffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 76 publications
1
0
0
Order By: Relevance
“…This resulted in less nitrite and nitrate, potentially explaining a portion of the observed among-site variation. This study complements and adds a layer of generality to previous studies suggesting significant effects of climate change on the more intensively studied prokaryotic communities ( Seidel et al, 2022a , b , 2023 ).…”
Section: Discussionsupporting
confidence: 71%
“…This resulted in less nitrite and nitrate, potentially explaining a portion of the observed among-site variation. This study complements and adds a layer of generality to previous studies suggesting significant effects of climate change on the more intensively studied prokaryotic communities ( Seidel et al, 2022a , b , 2023 ).…”
Section: Discussionsupporting
confidence: 71%
“…Both in the presence or absence of the invertebrate, the predicted functional changes were consistent with the observed changes in community structure but may also be related with short-term adaptations to distinct climate scenarios. For instance, in the case of a temperature increase to 15 • C-25 • C, a decrease in pathways related with carbohydrate metabolism may be part of a strategy to reduce heat generation [80]. Conversely, an increase in functions related to stress response, such as signal transduction pathways and cell mobility, was observed for this and other scenarios, both in the presence or absence of E. crypticus.…”
Section: Discussionmentioning
confidence: 87%
“…This decrease in diversity is detrimental to community health as a high diversity (combination of different species) buffers against environmental changes ( Elmqvist et al, 2003 ). For instance, an increase in temperature influences the microbial community composition and their energy- and nutrient cycling, which further impacts marine carbon cycling ( Abirami et al, 2021 ; Seidel et al, 2023a ). A decline in microbial diversity in the heated bay surface waters of this investigation is supported by previous studies of the heated bay benthic microbial communities ( Seidel et al, 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…The heated bay warming also leads to compression of sediment geochemical layers such that, e.g., the sulfate/methane transition zone occurs closer to the sediment surface along with shifts in seasonal bottom water microbial communities altering, e.g., the cyanobacterial bloom pattern ( Seidel et al, 2022a ). Furthermore, a laboratory-based thermal gradient study demonstrated the ability of the control and heated bay benthic community’s response to potential future marine heatwaves ( Seidel et al, 2023a ). The data show a broader thermal tolerance in the heated bay coupled with elevated RNA transcripts related to stress.…”
Section: Introductionmentioning
confidence: 99%